Preparation and characterization of RHA based ceramic membrane for gas leak testing in SOFC seals. Issue 1 (January 2022) - Gunawan,; Sulistyo,; Setiawan, I
Abstract: Solid Oxide Fuel Cell (SOFC) systems show great potential in future power generation applications. SOFC has many advantages, including high efficiency, low emission, and flexible modular structure. SOFC is an electrochemical device that converts fuel into electricity directly. If hydrogen gas is used, it will produce electricity and waste products in the form of heat and water vapor. The complete SOFC module system consists of a furnace, cell stack, fuel and oxygen. Several parameters that affect SOFC performance are fuel flow rate, furnace temperature, cell material, and collector current. SOFC consists of anode, electrolyte, cathode, and current collector. These parameters have a correlation with each other in building a SOFC system, resulting in a good cell and optimal output voltage. SOFC based on electrolyte material yttria stabilized zirconia (YSZ) operates at working temperatures between 600 to 1, 000°C, so all materials used must be able to withstand these temperatures. In the empirical case to separate each function of the components in the fuel cell, a sealant is needed. The sealant function prevents fuel and oxidant leakage in the stack and electrically isolates the cells in the stack. So the other sealant material requirements are to have thermal and chemical compatibility with other cell components, chemically and physically stable at high temperatures and have good mechanical strength. The composition of the material (RHA, CaO, Al2 O3, MgO and BaO) with six formulations (F1-F6) which was determined as a gas leak test specimen through a synthesis process using the ball mill method for 12 hours resulted in a grain variation between 3.808 um – 19.631 um. The production of gas leak test specimens was successfully carried out by molding which was designed to be effective using a material weight of 1.5 grams with a 96% PVA binder as much as 20% by weight. The size of the specimen obtained in the form of a membrane with a thickness of 1-1.1mm. The preparation of the test material can be continued in the next gas leak test process.